Literature, Geolocation and Wikidata - Nielsen, Finn (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Littar was the second-prize winning entry in an app competition. It implemented a system for visualizing places mentioned in individual literary works. Wikidata acted as the backend for the system. Here I describe the Littar system and also some of the issues I encountered while developing the system: How locations and literature can be related, what types of location-literature relations are possible within Wikidata, what limitations there are and what questions we may ask once we have enough data in Wikidata.